A note on Mexico’s growth - Ize, Alain (Estudios Económicos de El Colegio de México, 2019)
Building on a novel elasticities-based growth accounting decomposition, this note puts the insufficient dynamism of Mexico’s exports and the inertia of its segmented economy at the heart of its unsatisfactory per capita GDP growth. Boosting exports without exacerbating protectionism would require a shift toward more innovative products or with higher demand elasticities. This in turn would imply a greater shift toward a knowledge economy and exports of personal services. Making Mexico more attractive to people through strengthening the rule of law and preserving the country’s ecological and touristic capital should therefore be at the center of the country’s growth agenda.